Gastrointestinal parasites of common opossums (Didelphis marsupialis) in urban protected areas of Antioquia, Colombia - Hernández-Montoya, Viviana; Navarro-Ruiz, Leonardo; López-Osorio, Sara; Chaparro-Gutiérrez, Jenny J; Ceballos, Claudia P (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: The common opossum (Didelphis marsupialis) is a generalist species that hosts several parasites. Nevertheless, no information is available on the specific parasites that this species may host when it inhabits urban areas. Objective: To evaluate the presence and frequency of gastrointestinal parasites of urban opossums in the Aburrá Valley, Antioquia, Colombia. Methods: A total of 70 opossums were captured in six protected urban areas using Tomahawk traps during six months. From these animals we obtained 65 fecal samples which were fixed wit SAF solution and analyzed with direct smear and sedimentation techniques. Results: Sixty-one samples were positive for, at least, one parasite (93.9%) and 60 were positive for two or more parasites, averaging five parasites per animal. We observed nematodes in 58 samples (89.2%), protozoa in 46 samples (70.7%), acanthocephalans in 29 samples (44.6%), and cestodes in eight samples (12.3%). The most frequent parasite was Aspidodera spp. in 80% of the samples. In addition, this is the first study reporting the presence of eggs of Toxocara spp., Hymenolepis spp., an Oxyuridae parasite, and coccidians Eimeria didelphidis, E. caluromydis, and E. marmosopos in D. marsupialis. The latter is also reported in Colombia for the first time. Toxacara spp. is common to dogs and cats, while Hymenolepis and Oxiuridae are common to rodents. We found no association between parasites and sex or life stage of opossums, nor to the urban area of origin. Conclusions: Urban opossums in the Aburrá Valley host a high frequency and diversity of gastrointestinal parasites compared to other areas in Latin America. Some parasites are reported here for the first time.